2006
DOI: 10.1094/phyto-96-1214
|View full text |Cite
|
Sign up to set email alerts
|

Differential Selection on Rhynchosporium secalis During Parasitic and Saprophytic Phases in the Barley Scald Disease Cycle

Abstract: Competition among eight Rhynchosporium secalis isolates was assessed during parasitic and saprophytic phases of the disease cycle in field experiments conducted at two locations and over two growing seasons. The eight isolates were inoculated onto six barley populations exhibiting varying degrees of resistance. Microsatellite analysis of 2,866 isolates recovered from the field experiments showed significant, and sometimes opposite, changes in the frequencies of R. secalis genotypes during the growing season (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 35 publications
5
68
0
Order By: Relevance
“…"Mark-release-recapture" experiments based on artificial inoculations were performed with fungal pathogens of wheat, including Z. tritici (15,35,40,41; see also the reviews by Zhan and McDonald [16,17]). Under natural conditions, given the high diversity of Z. tritici populations (20), the earliest cohort of lesions is caused by different genotypes, and the probability of recapturing one of them on the upper leaves at the end of the epidemic is almost zero.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…"Mark-release-recapture" experiments based on artificial inoculations were performed with fungal pathogens of wheat, including Z. tritici (15,35,40,41; see also the reviews by Zhan and McDonald [16,17]). Under natural conditions, given the high diversity of Z. tritici populations (20), the earliest cohort of lesions is caused by different genotypes, and the probability of recapturing one of them on the upper leaves at the end of the epidemic is almost zero.…”
Section: Discussionmentioning
confidence: 99%
“…Further experimental investigations taking into account the pathogenic and saprophytic phases of the disease cycle (40,41), guided by theory (43,47), would be appropriate for characterizing the effect of seasonality on year-to-year disease transmission. Indeed, seasonality plays a role in short-term pathogen evolution by causing alternating periods of high transmission and population bottlenecks (8).…”
Section: Discussionmentioning
confidence: 99%
“…For these pathogens our results show that the length of the crop 23 growing season/length of the period of host absence is by far the key determinant of the 24 evolutionarily stable pathogen transmission rate. 25 26 For the group of soil borne plant pathogens the existence of the transmission survival trade-1 off is well established (Abang et al 2006;Bailey et al unpublished). We have, however, not 2 found any data suggesting the existence of a transmission-virulence trade-off for such 3 systems.…”
Section: Severity 4mentioning
confidence: 99%
“…Examples of breeding outcomes that utilize genotype diversity include composite crosses (synthetic landraces), cultivar mixtures, and cisgenic or transgenic multilines. Over the last 20 years, we conducted three different field experiments in three locations and with three different cereal pathogens that showed that 2-component cultivar mixtures can significantly slow pathogen evolution (Abang et al 2006;Sommerhalder et al 2011;Zhan et al 2002;Zhan & McDonald 2013a, b). The consistent findings in these experiments increase our confidence that breeding approaches that increase genotype diversity within fields will provide a significant step forward on the path towards durable resistance.…”
mentioning
confidence: 99%